EFEKTIVITAS PENERAPAN APLIKASI SIMBANGDA PADA BAGIAN KEUANGAN KANTOR DPRD PROVINSI SUMATERA BARAT - Nira Elsa Ramadhani; Nora Eka Putri (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
At present the use of information technology in government agencies is increasingly being found. One form of utilization of management information systems in government organizations is the Regional Development Information System (SIMBANGDA). SIMBANGDA application is software that is designed to simplify and integrate budget data available in each budget month to report on the development of financial realization and the state of physical realization of work carried out by the Regional Devices Organization (OPD). This research is a qualitative research with descriptive method. The informant of the research was conducted by Purposive Sampling. The technique of data collection is done by observation, interviews and documentation studies. The validity test of the data is done by source triangulation techniques, then the data is reduced and conclusions are drawn from the results of the study. The results of this study indicate that (1) consists of 3 indicators (a) In achieving the objectives it is still not maximal because there are still errors in the calculation of financial realization in the application. (c) and the adaptation of SIMBANGDA operators is still not maximal because there are still those who do not understand how to use SIMBANGDA Apps (2) the availability of sufficient hardware and software and (3) there are still operator errors in the data entry process.